Contribution of foreign direct investment to poverty reduction : the case of Vietnam in the 1990s - Hemmer, Hans-Rimbert; Phuong Hoa, Nguyen Thi; Justus Liebig University Giessen (My University, 2002)
In the current context of increasing globalisation, there exist many arguments against it in that it does not benefit the poor. Globalisation through foreign direct investment (FDI) might do nothing for the poor since foreign investors usually recruit skilled workers who are likely to be non-poor. FDI may outcompete local small enterprises making local workers become poor or the poor workers worse. Nevertheless, whether this presumption is true in every developing country is still open to discussion. The paper aims at analysing impacts of FDI on poverty reduction in Vietnam in the 1990s because following the economic reform in the late 1980s Vietnam achieved high economic growth, rapid poverty reduction, increasing FDI and trade. FDI is also considered an integral component of the economy. Hence to what extent FDI contributes to poverty reduction may be a relevant question to the country that was characterised by widespread poverty in the 1980s. The paper analyses FDI's impact on poverty reduction in Vietnam through direct and indirect impacts. The direct impact of FDI works through employment creation and it is estimated to be negative but insignificant. The indirect impact of FDI works throughFDI's effect on economic growth and through FDI's contribution to the local budgets. Regarding FDI's contribution to growth, estimated coefficients are significantly positive based on panel data covering 61 provinces of Vietnam and the 1990-2000 period. Furthermore, FDI interacts positively with local human capital in affecting economic growth. Economic growth is then estimated to exert significantly positive impacts on the magnitude of poverty reduction results. Therefore, FDI has indirectly helped reduce poverty in Vietnam. Regarding FDI s contribution to the local budget, this effect remains insignificant. Globalisation through FDI thus benefits the poor. Policy implications then include policies that help attract FDI continuously, policies that facilitate the implementation of registered foreign investment projects and policies that upgrade the quality of the labour workforce.
Keywords: ddc:650